SCHEMATIC STRUCTURE OF GUEST SPEAKERS’ SPEECHES AT A GHANAIAN UNIVERSITY - Emmanuel Kyei Emmanuel; Wilson Awiah Jujugenia; Joseph Benjamin Archibald Afful; Isaac N. Mwinlaaru; William Kudom Gyasi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
The present study explored the schematic structure in Guest Speakers’ Speeches (GSS) in a Ghanaian university. A total of 20 speeches was purposively collected between 2014 and 2020. We utilized the frameworks proposed by Swales (1990) and Bhatia (1993) in identifying the schematic structure of the speeches. The findings revealed a macro-structure of four (4) Moves (Welcome, Appreciation and Thanks, Teaching the last lesson and Closing moves). Among the moves, Teaching the Last Lesson occupied the greatest textual space (i.e. 78%) of the data. As regards the sequence of moves, the study revealed (1) that the 10-move sequence was the most frequent pattern; and (2) that the moves are chronologically structured, with Move 1 followed by Move 2, Move 3, and finally Move 4. The study validates guest speakers’ speeches as a conventionalized yet contextually adaptable genre that scaffolds graduates' identity transition. The findings advance genre research and inform professional practice in similar contexts.